PERAN ORANG TUA DALAM MENDAMPINGI ANAK DI RUMAH SELAMA PANDEMI COVID-19 - Selfi Lailiyatul Iftitah; Mardiyana Faridhatul Anawaty (Universitas Islam Lamongan, 2020)
The Covid 19 pandemic led to the issuance of learn from home rules for school children and work Â from home for teachers, including those who work in PAUD institutions. The current situation demands maximum parental involvement and restores the nature of children's education in the family. This article will discuss the role of parents in accompanying children at home during a pandemic. The method used is the literature study method with data collection using documentation from theoretical studies obtained from books and journals. Since the Covid 19 pandemic, children's education has been carried out remotely. Learning carried out at home makes the role of parents very important. During the Covid-19 pandemic, parents not only functioned as the first and foremost place for children's education in shaping character, religious values and character but now have an additional role as second teacher for children in learning at home. Accompanying children when learning is something that is very important for children, namely to build closeness between parents and children. As for the important role of parents in accompanying children, namely children feel not alone, parents as encouragement, facilitate children's needs, a place to discuss and ask questions, help identify.